The Strength of Predict, Organize, Rehearse, Practice, Evaluate With Kahoot in The Teaching Reading for Junior High School - Varia Virdania Virdaus; Saiful Rifa’i (Journal of Development Research, 2023)
The purpose of this study was to determine how well junior high school reading instruction using Kahoot and PORPE (Predict, Organize, Rehearse, Practice, Evaluate) works. This study employed a quasi-experimental method. The research sample consisted of forty-one students, with eighteen students serving as the experimental class and twenty-three students serving as the control group. The subjects of in this study were students VIII A and VIII B SMP Alam Al-Ghifari. The researcher applied ANCOVA to calculate the data. The teaching reading using the Predict, Organize, Rehearse, Practice, Evaluate With Kahoot on students' reading comprehension revealed that the value of F= 29.591. and 0.000 was displayed by the probability (P). Using the PORPE method With Kahoot, the class's Kahoot score was 77.529. The class using the conventional method yielded 58.117. This indicates that the PORPE method using Kahoot produced superior results with a 95% confidence level. It is possible to get the conclusion that the PORPE method combined with Kahoot worked well for teaching reading.